Global Scientific Production on Stakeholder Engagement in Community Forestry: A Bibliometric Analysis - Afrianto, Whisnu Febry (Foresty Faculty of Hasanuddin University, 2025)
Community forestry is a concept that presents management and utilization rights to local communities through empowering communities in sustainably managing forest resources and engaging them in forest conservation movements. This study aims to investigate the scope of stakeholder engagement in community forestry using a bibliometric review. Understanding stakeholders' participation in community forest management through a 30-year bibliometric analysis is essential for achieving historical insights, deciding conflicts, and discussing global forest landscape topics. The data was obtained from the Scopus database. Analysis of references with 808 publications and an annual publication growth rate of 6.49% (1981 – 2023) was used to identify the most significant sources of stakeholder engagement in global trends. Topic areas with titles, keywords, and abstracts in stakeholder engagement in community forestry themes were utilized as a reference for exploring search results. This present study analysed bibliometrics using VOSviewer and Biblioshiny. The publication reached the highest number with 64 publications in 2020. Peter A. Minang was the most productive author in the discipline, with an h-index of 9, total publications of 9, and worldwide citations of 394 from 2005 to 2023. The United States of America (USA) dominated the most publications on this topic. Furthermore, Tribhuvan University was the most relevant affiliated institution. The most productive journal in this field was Forest Policy and Economics. This investigation delivers scholarly novelty in evaluating Global Community Forestry publications, which are practically and theoretically essential to regulators, academia and industry professionals. These findings are important as a foundation for several suggestions for future stakeholder engagement in community forestry research.